2022
DOI: 10.1038/s41419-022-04848-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cancer stemness maintenance in human liver cancer

Abstract: Primary liver cancer mainly includes the following four types: hepatocellular carcinoma (HCC), cholangiocarcinoma (CCA), hepatoblastoma (HB), and combined hepatocellular carcinoma and cholangiocarcinoma (cHCC-CCA). Recent studies have indicated that there are differences in cancer stem cell (CSC) properties among different types of liver cancer. Liver cancer stem cells (LCSCs), also called liver tumor-initiating cells, have been viewed as drivers of tumor initiation and metastasis. Many mechanisms and factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 106 publications
0
13
0
Order By: Relevance
“…Recent studies have confirmed the effect of tumor stemness on immune cells in tumor microenvironment, namely, tumor-associated macrophages (TAMs), myeloid-derived suppressor cell (MDSC), and CD8 + T cells. In turn, these immune cells also play an important role in maintaining tumor stemness, creating a malignant environment [ 8 ]. However, there are few studies on tumor stemness in HCC, especially the relationship between tumor stemness and immune microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have confirmed the effect of tumor stemness on immune cells in tumor microenvironment, namely, tumor-associated macrophages (TAMs), myeloid-derived suppressor cell (MDSC), and CD8 + T cells. In turn, these immune cells also play an important role in maintaining tumor stemness, creating a malignant environment [ 8 ]. However, there are few studies on tumor stemness in HCC, especially the relationship between tumor stemness and immune microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…CSCs are considered to be responsible for cancer initiation and progression 4 . Thus, we explored the effect of RAB6A KD on the stem cell properties of CCA cells.…”
Section: Resultsmentioning
confidence: 99%
“…CSCs are considered to be responsible for cancer initiation and progression. 4 Thus, we explored the effect of RAB6A KD on the stem were observed in tumor cells in the shRAB6A group. Collectively, these data suggest that RAB6A KD inhibits tumor growth in vivo.…”
Section: Rab6a Kd Inhibits Stem Cell Properties and Epithelial−mesenc...mentioning
confidence: 99%
See 1 more Smart Citation
“…Original Article Identification of immune-related genes and patient selection for hepatocellular carcinoma immunotherapy However, alternative treatment methods for patients with unresectable middle and advanced HCC are limited, and new treatment strategies are urgently needed (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%